IMPLEMENTING ISLAMIC RELIGIOUS EDUCATION IN VOCATIONAL SCHOOLS' CURRICULA - Destriani; Maria Botifar; Deri Wanto (Jurnal Ilmiah Pendidikan Citra Bakti, 2023)
The curriculum has an important role in achieving learning goals. If in a drama then, the curriculum is used as a scenario. The curriculum has 4 basic components namely, objectives, materials, process and evaluation. These four components cycle with each other and synergize with each other to achieve learning objectives. Islamic religious education is one of the scientific clusters aimed at character development. This study uses a qualitative research methodology with the type of field research. The ideal curriculum is a curriculum that is clearly visible, such as lesson plans and syllabus, the implementation of the curriculum for Islamic religion education is intended to make the curriculum an important part of student development.